2013
DOI: 10.2109/jcersj2.121.831
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced alignment controls of one-dimensional mesochannels in mesoporous materials

Abstract: Mesoporous materials prepared through the self-assembly of surfactants have attracted wide attention because of their many potential applications. The mesostructural, compositional, and morphological controls of mesoporous materials have been extensively studied thus far. In particular, the macroscopic alignments of one-dimensional (1D) mesochannels and their controls are quite important for the creation of advanced functional materials. In most cases, the direction of mesochannels in mesoporous films lies par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 96 publications
1
85
1
Order By: Relevance
“…Therefore a great deal of research has been conducted to enhance the TiO 2 performances in the solar spectrum by the selection of suitable photocatalyst support and doping agents [5][6][7][8][9]. The photocatalytic performance of TiO 2 depends on its crystal structure, particle size as well as effective surface area, and therefore with the use of nano-sized TiO 2 the number of particles per unit area is increased enhancing its photocatalytic activity in the UV light [10][11][12][13][14][15]. Unfortunately, using the nanosized TiO 2 has disadvantages related to health hazards by the inhalation toxicity [16] and possible nanoparticle aggregation that decreases the overall activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a great deal of research has been conducted to enhance the TiO 2 performances in the solar spectrum by the selection of suitable photocatalyst support and doping agents [5][6][7][8][9]. The photocatalytic performance of TiO 2 depends on its crystal structure, particle size as well as effective surface area, and therefore with the use of nano-sized TiO 2 the number of particles per unit area is increased enhancing its photocatalytic activity in the UV light [10][11][12][13][14][15]. Unfortunately, using the nanosized TiO 2 has disadvantages related to health hazards by the inhalation toxicity [16] and possible nanoparticle aggregation that decreases the overall activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…163,164 Thanks to their fascinating physicochemical properties, such as high electrical and thermal conductance, mesoporous metals offer a wider range of potential applications in bio-sensing, surface-enhanced Raman scattering, surface plasmon resonance, hydrogen storage and catalysis. It has been experimentally and theoretically demonstrated that the morphology and structure of mesoporous metals strongly affect their physical and chemical properties.…”
Section: Lyotropic Liquid Crystalsmentioning
confidence: 99%
“…23 Tunable textural properties, high surface area, and pore volume are typical properties of mesoporous materials, which make them suitable candidates for drug-delivery purposes. [24][25][26][27][28][29][30] For example, a sustained release of cephalothin from mesoporous titania-coated implants in vitro has recently been reported. 31 Moreover, Se Park et al have demonstrated that the sustained release of high dosages of cephalothin and amoxicillin from mesoporous titania surfaces reversed the functions of five different bacterial species.…”
Section: Introductionmentioning
confidence: 99%